Regarding Tobias Peucer’s Dissertation on Journalism. A Philosophical Perspective - Munteanu, Cristinel (Acta Universitatis Danubius. Communicatio, 2023)
In 1690, in Leipzig, Tobias Peucer defended the first doctoral thesis (in the world) devoted to journalism, namely De relationibus novellis (“On news reporting”). In this article, I aim at proving the validity and durable value of Peucer’s dissertation, by analysing its content and structure, while also taking into account the philosophical aspects of this very important text, which establishes the theoretical foundation of journalism itself. In this regard, I will refer to some essential distinctions made by Aristotle, Kant and Coseriu, in order to demonstrate Peucer’s solid philosophical background and his right scientific intuitions.